2015
DOI: 10.18632/oncotarget.3246
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester induced cell cycle arrest and growth inhibition in androgen-independent prostate cancer cells via regulation of Skp2, p53, p21Cip1 and p27Kip1

Abstract: Prostate cancer (PCa) patients receiving the androgen ablation therapy ultimately develop recurrent castration-resistant prostate cancer (CRPC) within 1–3 years. Treatment with caffeic acid phenethyl ester (CAPE) suppressed cell survival and proliferation via induction of G1 or G2/M cell cycle arrest in LNCaP 104-R1, DU-145, 22Rv1, and C4–2 CRPC cells. CAPE treatment also inhibited soft agar colony formation and retarded nude mice xenograft growth of LNCaP 104-R1 cells. We identified that CAPE treatment signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 101 publications
(162 reference statements)
4
48
0
Order By: Relevance
“…Arsenic trioxide exhibited its antitumor activity via suppression of Skp2 in pancreatic cancer cells (52). Caffeic acid phenethyl ester suppressed cell proliferation and arrested the cell cycle through inactivation of Skp2 in prostate cancer cells (53). Notably, multiple natural agents have been characterized as Skp2 inhibitors (53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic trioxide exhibited its antitumor activity via suppression of Skp2 in pancreatic cancer cells (52). Caffeic acid phenethyl ester suppressed cell proliferation and arrested the cell cycle through inactivation of Skp2 in prostate cancer cells (53). Notably, multiple natural agents have been characterized as Skp2 inhibitors (53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Caffeic acid phenethyl ester suppressed cell proliferation and arrested the cell cycle through inactivation of Skp2 in prostate cancer cells (53). Notably, multiple natural agents have been characterized as Skp2 inhibitors (53)(54)(55)(56). Flavokawain A (FKA) selectively inhibited Skp2 in a proteasome-dependent manner in prostate cancer (57).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, compounds that can trigger the expression of tumor suppressor proteins are likely to inhibit the development and transformation of cells into cancerous ones [114] . In a recent study, caffeic acid phenyl esters has been shown to arrest castration resistant prostate cancer (CRPC) cells in the G0/G1 phase of the cell cycle by upregulating p53, p21 and p27 proteins [115]. Confirming this data, knocking down these tumor suppressors using siRNA attenuated the efficacy of caffeic acid phenyl esters [115].…”
Section: Mechanism Of Actionmentioning
confidence: 92%
“…In a recent study, caffeic acid phenyl esters has been shown to arrest castration resistant prostate cancer (CRPC) cells in the G0/G1 phase of the cell cycle by upregulating p53, p21 and p27 proteins [115]. Confirming this data, knocking down these tumor suppressors using siRNA attenuated the efficacy of caffeic acid phenyl esters [115]. Similarly, an increase in the expression of p53 was observed when cervical cancer cells were exposed to caffeic acid [116].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Both miR-150 [200] and miR-24 [201] suppresses the expression of p27 among xenograft mice, playing a contributing role on prostate oncogenesis and progression. Besides, administration of a novel compound CAPE displays beneficial anti-tumor effects in prostate cancer cells, primarily via reactivation and nuclear translocation of p27 [202]. Thus, all these evidences suggest that p27-targeted therapy is of great clinical potential as an anti-neoplastic strategy.…”
Section: Functions Of Ampk Signaling Components In Tumorigenesismentioning
confidence: 99%